PEMANFAATAN MEDIA PEMBELAJARAN CANVA DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK DI SMA ST. ANTONIUS BANGUN MULIA MEDAN - Febriola Sitinjak; Mariani Meri Lumban Gaul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the use of Canva learning media in improving students’ learning interest in Catholic Religious Education at SMA St. Antonius Bangun Mulia Medan. The research was conducted due to the low level of students’ learning interest, which was characterized by passive participation, low attention, and limited enthusiasm during classroom learning. This study used a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The research informants consisted of one Catholic Religious Education teacher, eight grade XI students, and one school principal. Data validity was ensured through source and technique triangulation. The results show that the use of Canva improves students’ learning interest, reflected in increased enjoyment, participation, curiosity, and attention during learning activities. Canva also supports teachers in presenting learning materials in a more structured, visual, and interactive form, which helps students understand the content more effectively. In addition, the findings align with previous studies that highlight the effectiveness of digital and visual learning media in enhancing student engagement. Therefore, Canva contributes as an effective learning media in creating more interactive and meaningful Catholic Religious Education learning.